2007
DOI: 10.1038/sj.gene.6364424
|View full text |Cite
|
Sign up to set email alerts
|

Monocytosis in BXSB mice is due to epistasis between Yaa and the telomeric region of Chromosome 1 but does not drive the disease process

Abstract: The BXSB murine model of systemic lupus erythematosus is differentiated from other murine models of lupus by a severe monocytosis. The recently identified Y-linked autoimmune accelerator locus, Yaa, which is fundamental to accelerated disease in male BXSB mice, is required for the monocytic phenotype in BXSB. It has also recently been shown to induce monocytosis in combination with the Nba2 locus from NZB. To dissect the genetic basis and associated pathogenicity of BXSB-related monocytosis, a panel of existin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Monocytosis might play an important role in the disease development of BXSB mice. 1216 Our data revealed severe monocytosis developed (approximately 40% in the spleen), and decreased significantly after As 4 S 4 treatment. The result suggests that arsenic might play a pivotal role in cell apoptosis induction and autophagy, through which monocytes were the major target.…”
Section: Discussionmentioning
confidence: 52%
“…Monocytosis might play an important role in the disease development of BXSB mice. 1216 Our data revealed severe monocytosis developed (approximately 40% in the spleen), and decreased significantly after As 4 S 4 treatment. The result suggests that arsenic might play a pivotal role in cell apoptosis induction and autophagy, through which monocytes were the major target.…”
Section: Discussionmentioning
confidence: 52%
“…In mice, Kikuchi et al (2006) found clear association between percentages of monocytes and serum levels of anti-nuclear antibodies; monocyte levels at 10 months of age and lethal nephritis by 18 months of age were correlated. Rogers et al (2007) observed that monocytosis was closely associated with autoantibody production in NZB but not BXSB mouse models. In our rabbit model, homozygosity for the Ig heavy chain haplotype with the VH1a1 allotype allele correlated with enhanced WBC and monocyte responses suggesting genetic influences of these traits.…”
Section: Discussionmentioning
confidence: 92%
“…S3). Second, the major susceptibility loci associated with autoimmune disease in this model have been rigorously mapped and none are located near Il21r (23,24). IL-21 signaling is therefore fundamental to one or more critical steps in the pathogenesis of SLE in BXSB-Yaa mice.…”
Section: Discussionmentioning
confidence: 99%